The genetic architecture of photosynthesis and plant growthrelated traits in tomato - Oliveira Silva, Franklin Magnum de; Lichtenstein, Gabriel; Alseekh, Saleh; Rosado‐Souza, Laise; Conte, Mariana; Fuentes Suguiyama, Vanessa; Lira, Bruno Silvestre; Fanourakis, Dimitrios; Usadel, Björn; Lopes Bhering, Leonardo; DaMatta, Fábio M.; Sulpice, Ronan; et al. (Wiley, 2022)
To identify genomic regions involved in the regulation of fundamental physiological processes such as photosynthesis and respiration, a population of Solanum pennellii introgression lines was analyzed. We determined phenotypes for physiological, metabolic, and growth related traits, including gas exchange and chlorophyll fluorescence parameters. Data analysis allowed the identification of 208 physiological and metabolic quantitative trait loci with 33 of these being associated to smaller intervals of the genomic regions, termed BINs. Eight BINs were identified that were associated with higher assimilation rates than the recurrent parent M82. Two and 10 genomic regions were related to shoot and root dry matter accumulation, respectively. Nine genomic regions were associated with starch levels, whereas 12 BINs were associated with the levels of other metabolites. Additionally, a comprehensive and detailed annotation of the genomic regions spanning these quantitative trait loci allowed us to identify 87 candidate genes that putatively control the investigated traits. We confirmed 8 of these at the level of variance in gene expression. Taken together, our results allowed the identification of candidate genes that most likely regulate photosynthesis, primary metabolism, and plant growth and as such provide new avenues for crop improvement.